Exploring the Behavioural Intention in Culinary Tourism: A Study on Bandung Tourist Destination - Kusumawardani, Kunthi A.; Putri, Fadhilah R. (Prasetiya Mulya Publishing, 2020)
This study portrayed the integration of behavioural theory and brand equity theory in the culinary tourism industry. This research aimed to find out the influence of a brand image, brand value, loyalty, and perceived quality towards motivation and behavioural intention in one of the most heavily promoted gastronomy destinations in Indonesia, the city of Bandung. This study used quantitative methods with a questionnaire as the research instrument and 282 Indonesian tourists as a sample. To test the measurement model and the theoretical framework, this research applied the Structural Equation Modelling (SEM). The result indicated that brand image, loyalty, and perceived quality positively influenced tourist motivation and behavioural intention. Nevertheless, the brand value was not found to have any significant influence in motivating tourists to come to Bandung for culinary tourism.